How Much Do Trading Partners Matter for Economic Growth? - Arora, Vivek; Vamvakidis, Athanasios (Washington, D.C. : International Monetary Fund, 2004)
This paper empirically examines the extent to which a country's economic growth is influenced by its trading partner economies. Panel estimation results based on four decades of data for over 100 countries show that trading partners' growth and relative income levels have a strong effect on domestic growth, even after controlling for the influence of common global and regional trends. One interpretation is that conditional convergence is stronger, the richer are a country's trading partners. A general implication of the results is that industrial countries benefit from trading with developing countries, which grow rapidly, while developing countries benefit from trading with industrial countries, which have relatively high incomes.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: United Kingdom